A stand-alone magnetic guide for producing tuneable radical beams dataset - Miossec, C; Wu, L Y; Bertier, P; Hejduk, M; Toscano, J; Heazlewood, B R (University of Oxford, 2020)
Raw data, simulations and analysis code for the evidence presented in the paper "A stand-alone magnetic guide for producing tuneable radical beams" by Chloe Miossec, Lok Yiu Wu, Paul Bertier, Michal Hejduk, Jutta Toscano and Brianna R. Heazlewood published in J. Chem. Phys. (2020).